ANALYSIS OF FINANCIAL PERFORMANCE AT PT. BANK MUAMMALAT INDONESIA Tbk. (2016-2018 PERIOD) - Khairun Nisa Panjaitan; Kasmawati Kasmawati; Syamsul Bahri (Jurnal Riset Manajemen Indonesia, 2020)
This study aims to interpret or interpret financial performance based on the ratio of Risk Profile, Good Corporate Governance, Earning, and Capital (Case Study of Bank Muammalat Indonesia Tbk). Analysis of the data used in this study using descriptive data methods. The results showed that the performance appraisal using the RGEC method in outline could be stated that PT. Bank Muammalat Indonesia Tbk is a fairly healthy bank. The assessment of bank performance at PT. Bank Muammalat Indonesia Tbk in 2014-2019 is viewed from the aspect of assessment by the RGEC method for Capital, namely the CAR ratio is classified as very adequate, which means that the level of capital is significantly higher than the applicable regulations.